Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae) - Ferguson, David J.; Yeates, David K. (Zootaxa, 2018)
The Apioceridae (Diptera) are relatively large asiloid flies with just over 140 described species worldwide. They are closely related to both Mydidae and Asilidae, and most species are found in Australia and North America, however a handful are found in both southern Africa and southern South America. The immature stages of only one species is known, the Australian beach dune inhabiting species Apiocera maritima Hardy. Like most asiloid larvae, apiocerid larvae are assumed to be predators of other soft-bodied invertebrates in the soil. Anatomically the larvae and pupae are similar to those of closely related families. The larvae are elongate, cream-coloured, subcylindrical and with a small, well-sclerotised head capsule. The pupa has a number of robust processes and spines on the head capsule and rows of distinctive bristles on the abdominal tergites. These spines and bristles are used by the pupa to drill upwards out of the soil prior to adult emergence. Here we describe the late instar larva and pupa of the Australian species A. striativentris Paramonov and compare them to the larva and pupa of the previously described species. Apiocerid larvae have distinctive, rounded abdominal segments 2-5 that may be diagnostic for the family.